2013
DOI: 10.1021/ic402415b
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Two Different Ni2Zn Complexes with an Unprecedented Cocrystal Formed by One of Them and a “Coordination Positional Isomer” of the Other

Abstract: A new homometallic trinuclear Ni(II) complex [(NiL)2Ni(NCS)2] (1) and three heterometallic trinuclear Ni(II)-Zn(II)-Ni(II) complexes [(NiL)2Zn(NCS)2] (2), [(NiL)2Zn(NCS)2(CH3OH)2]·2CH3OH (3) and {[(NiL)2Zn(NCS)2(CH3OH)2]} {[(NiL)2Zn(NCS)2]} (4) have been synthesized by using the "complex as ligand" approach with the "metalloligand" [NiL] (H2L = N,N'-bis(salicylidene)-1,3-propanediamine) and thiocyanate in different ratios. All the complexes have been structurally and magnetically characterized. In the isomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Complex 2 crystallizes in the C 2 /c space group of the monoclinic system, and the crystal structure indicated that complex 2 contains three discrete neutral dinuclear 2 A, 2 B and 2 C units (Figure 6a), [ 1,2 ] at the same time, three crystallized CHCl 3 and one CH 3 OH. Each unit contains one completely deprotonated ligand (L) 3− , two Zn (II) ions in N 2 O 3 coordination environment, one μ ‐OMe − anion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Complex 2 crystallizes in the C 2 /c space group of the monoclinic system, and the crystal structure indicated that complex 2 contains three discrete neutral dinuclear 2 A, 2 B and 2 C units (Figure 6a), [ 1,2 ] at the same time, three crystallized CHCl 3 and one CH 3 OH. Each unit contains one completely deprotonated ligand (L) 3− , two Zn (II) ions in N 2 O 3 coordination environment, one μ ‐OMe − anion.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, two novel dinuclear Ni (II) and Zn (II) salamo-type complexes [Ni 2 L(MeOH)(μ-OAc)]Á 2CHCl 3 (1) and [{Zn 2 L(μ-MeO)} 3 ]Á3CHCl 3 ÁCH 3 OH (2), have been successfully synthesized by wet-chemical method. Complex 1 consists of two closely related dinuclear 1A and 1B units, and complex 2 consists of three closely related dinuclear 2A, 2B and 2C units, which are unique example of complexes formed by crystallographically independent but chemically identical molecules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations